Self-confirming immigration policy - Paolo E. Giordani; Michele Ruta (Center for Economic Studies and ifo Institute (CESifo), 2012)
We study immigration policy in a small receiving economy under self-selection of migrants. We show that a non-discriminatory immigration policy choice affects and is affected by the migratory decisions of skilled and unskilled foreign workers. From this interaction multiple equilibria may arise, which are driven by the natives' expectations on the welfare effects of immigration. In particular, pessimistic (optimistic) beliefs induce a country to impose higher (lower) barriers to immigration, which crowd out (crowd in) skilled migrants and thus confirm initial beliefs. This self-fulfilling mechanism sustains the endogenous formation of an anti or pro-immigration prejudice. We discuss how the adoption of a skill-selective policy affects this result.
Keywords: F22; J24; J61; 330; immigration policy; skilled/unskilled workers; small economy; multiple equilibria; Einwanderung; Migrationspolitik; Qualifikation; Migranten; Meinung; Kleines-Land-Modell; Theorie